Building Objects Out of Plato: Applying Philosophy, Symbolism, and Analogy to Software Design. - Giguette, Ray (Communications of the ACM, 2006)
The author argues for the application of philosophy, literary textual analysis and analogy analysis to the designing of computer software. The article uses Edgar Allen Poe's "The Raven" and Ernest Hemingway's "The Old Man and the Sea" as examples. The author constructs charts that link the symbols of the various works of literature to "object-orientated terminology." The author argues that by attempting to determine what specific parts of software code symbolizes, greater understanding of the purpose of computer software may be ascertained.